2010
DOI: 10.1007/s15010-010-0039-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term protection against hepatitis B after newborn vaccination: 20-year follow-up

Abstract: Our results show that combined active-passive immunization of newborns against hepatitis B provides persistent protection up to adolescence despite a frequent waning of anti-HBs antibodies, suggesting there is no need for booster vaccination during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 12 publications
3
29
0
2
Order By: Relevance
“…In completed vaccinees, anti-HBc seroconversion has been found in 1.5% from 3-15 years of age 40 and in 8% 15 years later, 46 although none became chronic carriers. However, among complete vaccines in Taiwan, 1.3% were HBsAg positive at age 2-6 years, while the figure was 4.5% among incomplete vaccinees, 39 and 1.3% to 3.5% of the immunized infants became HBsAg carriers 15 years later.…”
Section: Infection Rate In Vaccinated Populationsmentioning
confidence: 98%
See 2 more Smart Citations
“…In completed vaccinees, anti-HBc seroconversion has been found in 1.5% from 3-15 years of age 40 and in 8% 15 years later, 46 although none became chronic carriers. However, among complete vaccines in Taiwan, 1.3% were HBsAg positive at age 2-6 years, while the figure was 4.5% among incomplete vaccinees, 39 and 1.3% to 3.5% of the immunized infants became HBsAg carriers 15 years later.…”
Section: Infection Rate In Vaccinated Populationsmentioning
confidence: 98%
“…In a study on 640 children born to HBsAg positive mothers and with completed vaccination, protective anti-HBs was 93% afterwards, then falling to 70%, 40% and 25% at 5, 10, and 15 years of age respectively. 40 Another study on 1095 subjects with early childhood vaccination and assessed at age 1-24 years found that while overall efficacy against infection and carriage were 83.4% and 96.5% respectively, population vaccine efficacy against infection decreased from 92.5% among 1-4 years old to 70.9% among 20-24 years old, and efficacy against carriage decreased from 100% to 91.1%. 41 When tested at specific ages, a significant waning in anti-HBs titer can be found at age 15 to 18 years.…”
Section: Waning Of Anti-hbs Titer With Advancing Agementioning
confidence: 99%
See 1 more Smart Citation
“…In completed vaccinees, anti-HBc seroconversion has been found in 1.5% from 3-15 y of age 4 and in 8% 15 y later, 5 even though none of the subjects in these reports became chronic carriers at the time of the study. In Taiwan, 1.3% and 4.5% of complete and incomplete vaccinees respectively were HBsAg positive at age 2-6 y, 6 and 1.3% to 3.5% of immunized infants became HBsAg carriers 15 y later.…”
Section: Sirmentioning
confidence: 85%
“…15 There is no dispute that following vaccination, antibody titer also falls with age, as shown in a study on 640 children with complete vaccination and born to HBsAg positive mothers that protective anti-HBs dropped from the initial 93% to 70%, 40% and finally 25% when tested at 5, 10, and 15 y of age respectively. 4 Another study also found that the percentage of protected individuals decreased with time with significant reduction of antiHBs GMT after 5 y to reach 10 mIU/mL in about 15 years' time. 16 The worst scenario was in Micronesians, as only 7.3% of uninfected individuals vaccinated at birth had antibody protection.…”
Section: Sirmentioning
confidence: 90%